The Roadmap Policy of Junior High School Education in Maybrat Regency: A Qualitative Multi-Case Study on Planning, Implementation, and Evaluation in a 3T Context - Kornelius Kambu; Jeffry Sony Junus Lengkong; Joulanda A M Rawis; Rolles N. Palilingan (JR Education, 2025)
This study examines the planning, implementation, and evaluation of the Junior High School (SMP) Education Roadmap Policy in Maybrat Regency an Indonesian region categorized as 3T (frontier, outermost, underdeveloped). The study responds to persistent disparities in educational access and quality that are strongly shaped by geographic isolation, uneven teacher distribution, infrastructure gaps, and limited digital readiness. Using a qualitative multi-case design, data were collected through in-depth interviews with key actors (regional head, education office leadership, school principals, teachers, and community representatives), observations, and document analysis across SMP settings. Evidence indicates that the policy planning process has been initiated in a participatory manner and anchored in the region’s medium-term development direction; however, it remains insufficiently integrated with broader regional planning documents and is weakened by data validity constraints arising from uneven data synchronization practices. Implementation has shown tangible governmental commitment through infrastructure development, teacher contracting, local BOS strengthening, scholarships, and teacher training; nevertheless, implementation performance is constrained by structural and managerial challenges particularly shortages of subject teachers, transportation barriers, low parental participation, limited ICT facilities, and low digital literacy. Evaluation practices tend to emphasize administrative reporting rather than outcome-based learning improvements; although national instruments such as the Education Report Card (Rapor Pendidikan) have begun to be used, they are not yet fully integrated into iterative policy refinement. The findings suggest that strengthening evidence-based planning, ensuring consistent implementation mechanisms, improving inter-agency coordination, and adopting comprehensive outcome-oriented evaluation are critical for transforming the roadmap into an effective regional education governance instrument in 3T settings.